(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: Emotional Intelligence (EI) is recommended as one of the metrics that predicts a person’s overall growth and achievement. A nurse with strong emotional intelligence may find it easier to maintain and enhance self-control and confidence. Objective: The study aimed to evaluate the level of emotional intelligence and its role in academic success among undergraduate nursing students. Methodology: The analytical cross-sectional study was conducted at six nursing institutions (three public and three private) from November 2024 to February 2025 in Karachi, Pakistan. The sample size was calculated by Open Epi version 3.0. The data were collected from 378 undergraduate nursing students by using an open-ended, validated, and structured questionnaire, named the Schutte Self-Report Emotional Intelligence Test (SSEIT), through a multistage sampling technique. All male and female undergraduate nursing students above than 16 years of age currently enrolled in the 5th, 6th, 7th, and 8th semester of Bachelor of Science in Nursing (GBSN) program were included while all other students of midwifery, post RN, technicians and students from other disciplines were excluded from the study. Results: Among total participants, 57.8% had average EI, 28.8% had low EI, and surprisingly, only 13.4% reported a high level of EI. Furthermore, a weak positive correlation (ρ = 0.142, p-value = 0.006) between intelligence scores and CGPA was found. Conclusion: The study concludes that Emotional Intelligence (EI) among undergraduate nursing students is mainly average, with a surprisingly lower proportion of EI.